Orchestration : the movement and vocal behavior of free-ranging Norwegian killer whales (Orcinus orca) - Shapiro, Ari Daniel (Massachusetts Institute of Technology, 2008)
Thesis (Ph. D.)--Joint Program in Oceanography/Applied Ocean Science and Engineering (Massachusetts Institute of Technology, Dept. of Biology; and the Woods Hole Oceanographic Institution), 2008. Includes bibliographical references. Studying the social and cultural transmission of behavior among animals helps to identify patterns of interaction and information content flowing between individuals. Killer whales are likely to acquire traits culturally based on their population-specific feeding behaviors and group-distinctive vocal repertoires. I used digital tags to explore the contributions of individual Norwegian killer whales to group carousel feeding and the relationships between vocal and non-vocal activity. Periods of tail slapping to incapacitate herring during feeding were characterized by elevated movement variability, heightened vocal activity and call types containing additional orientation cues. Tail slaps produced by tagged animals were identified using a rapid pitch change and occurred primarily within 20m of the surface. Two simultaneously tagged animals maneuvered similarly when tail slapping within 60s of one another, indicating that the position and composition of the herring ball influenced their behavior. Two types of behavioral sequence preceding the tight circling of carousel feeding were apparent. First, the animals engaged in periods of directional swimming. They were silent in 2 of 3 instances, suggesting they may have located other foraging groups by eavesdropping. Second, tagged animals made broad horizontal loops as they dove in a manner consistent with corralling. All 4 of these occasions were accompanied by vocal activity, indicating that this and tail slapping may benefit from social communication. No significant relationship between the call types and the actual movement measurements was found. Killer whale vocalizations traditionally have been classified into discrete call types. Using human speech processing techniques, I considered that calls are alternatively comprised of ...